2021
DOI: 10.1039/d1ra01552d
|View full text |Cite
|
Sign up to set email alerts
|

Study of catalytic hydrogenation and dehydrogenation of 2,3-dimethylindole for hydrogen storage application

Abstract: The hydrogenation and dehydrogenation of 2,3-dimethylindole was studied. The released hydrogen was in a high purity, detected by DSMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…34 However, when the Pd/Al 2 O 3 catalyst was reused in the dehydrogenation reaction after a longer reaction time (12 h), obvious catalyst degradation was observed due to carbon formation on the Pd surface and metal agglomeration. 35 As reported by Wang and Dyson in 2020, bimetallic Pd-Au NPs supported on multi-wall carbon nanotubes (CNTs) exhibited generally high yields (>90%) in the reversible dehydrogenation and hydrogenation of heterocyclic compounds, amines/imines, and alcohols/ketones. 202 DFT calculations showed that the Pd 3 Au 1 (111) facet leads to lowerenergy barriers than those observed on the Pd (111) surface for the elementary steps in both dehydrogenation and hydrogenation reactions of indole derivatives.…”
Section: Derivativesmentioning
confidence: 79%
See 3 more Smart Citations
“…34 However, when the Pd/Al 2 O 3 catalyst was reused in the dehydrogenation reaction after a longer reaction time (12 h), obvious catalyst degradation was observed due to carbon formation on the Pd surface and metal agglomeration. 35 As reported by Wang and Dyson in 2020, bimetallic Pd-Au NPs supported on multi-wall carbon nanotubes (CNTs) exhibited generally high yields (>90%) in the reversible dehydrogenation and hydrogenation of heterocyclic compounds, amines/imines, and alcohols/ketones. 202 DFT calculations showed that the Pd 3 Au 1 (111) facet leads to lowerenergy barriers than those observed on the Pd (111) surface for the elementary steps in both dehydrogenation and hydrogenation reactions of indole derivatives.…”
Section: Derivativesmentioning
confidence: 79%
“…199 N-Substituted indole derivatives were also evaluated as another class of potential hydrogen carrier molecules. From 2015 to 2021, especially the group of Yang, Cheng, and Ke reported the catalytic hydrogenation of indole derivatives, e.g., N-ethylindole, 33 N-methylindole, 200 7-ethylindole, 201 1,2dimethylindole, 34 and 2,3-dimethylindole, 35 and the reverse reactions. In the temperature range of 120−200 °C, two different heterogeneous catalysts, Pd/Al 2 O 3 (5 wt%) and Ru/ Al 2 O 3 (5 wt%), were used in the corresponding (de)hydrogenation reactions, respectively.…”
Section: Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…For 2,3-dimethylindole, complete hydrogenation was achieved over 5 wt% Ru/Al 2 O 3 at 190 °C and 7 MPa in 4 h. Dehydrogenation of perhydro-2,3-dimethylindole was successfully performed over 5 wt% Pd/Al 2 O 3 at 180–210 °C and 101 kPa [ 14 ]…”
Section: Introductionmentioning
confidence: 99%